Evolução morfodinâmica e hidrológica direcionada ao manejo de lagoas costeiras tropicais. Estudo de caso : lagoa das almécegas, Paraipaba - Trairi/Ce - Silva, Raquel Lemos da (2007)
The coastal lagoon, Almécegas, are located in the coastal West of the State of the Ceará in the verge of the cities of Trairi and Paraipaba. The main objective of this work was to evaluate the evolution the controlling processes of the morphology and hidrology of the Lagoon of the Almécegas being aimed at to generate useful information to the use and management of this coastal hídrico resource. The origin of the lagoon of the Almécegas is subordinated to the climatic-natural behavior of the area, sufficiently influenced for the littoral dynamics. With genesis related to the transgression and regression processes of the sea, and slide bars of the extended river for the dune system (aeolian transport) and processes associated (fluvial discharge), being later with the construction of the barrage. The methodology used for accomplishment of this research is based inside on the understanding of the organization of the nature of the space, and the relation that occurs between its components. For they had been in such a way carried through you analyze of the physical and chemical parameters of the water: temperature, electric condutividade, turbidez, pH and transparency. Furthermore, had been collected samples of deep subsurface and for the inquiry of material in suspension. Also, it was become fullfilled sedimentation characterization, analyzes of organic substance and metal-traces (it has covered, cadmium and zinc) in the sediment, and the morfomêtrico study and batimétrico survey of the lagoon. The results demonstrate that the studied system presented related sazonal variation to the two distinct hidrológicos periods. The rainy period if characterized for more intense precipitations and lesser insolation, whereas the dry one presented greater insolation and greaters speeds of the winds, bringing direct consequences on the water level of the lagoon. The water column presented stratification (thermal) significant had mainly to the depth of the system, to the performance of the winds and transparency of the water column. The grain sized composition of the sediments of deep of the Lagoon of the Almécegas had resulted in six main classrooms: slightly gravelly sand (43.8%), sand (25%), fine sand (6.3%), muddy sand (6.3%), slightly gravelly muddy sand (6.3%), silt (6.3%) and sandy silt (6.3%). It is observed that the thick fractions of the sediment, greaters that 0,063mm, occur in the great majority of the samples, what it can is related to the silting. The distribution of the organic substance indicates the different degrees of aeration of the diverse areas of the sedimentation environment. How much to the morphology the lagoon presenting an area of 1,3km2, perimeter of 9,935Km, maximum width of 684m and length of 3,5km, Volume of 6.688.000m ³, maximum depth of 5,85m, average depth of 2,55m. The relevance of the volume classifies this reservoir as of capacity of satisfactory storage. In occupation terms, the lagoon meets with low real estate occupation, had mainly to little speculation. But, the occupations that already occur in the region exceed the limits taxes for the law (Areas of Permanent Preservation) already the occupation associated with the withdrawal of the vegetal covering are possible of being seen, and this problem can generate an instability of the edges and consequence the alteration of the morfométricas characteristics and physicistchemistries of the lagoon, being able to cause negative impacts, as increase of the superficial draining, erosion of the edges, greater arrives in port of sediments in the lagoon, assoreamento, reduction of the volume of water, and greater concentration of pollutants in the lagoon, being able to come also compromising the life of the population place.